Zirconia-supported rhenium oxide as an efficient catalyst for the synthesis of biomass-based adipic acid ester. Issue 74 (19th August 2019) - Lin, Jinchi; Song, Haiyan; Shen, Xiaoru; Wang, Binju; Xie, Shunji; Deng, Weiping; Wu, Deyin; Zhang, Qinghong; Wang, Ye
Abstract : ZrO2 -Supported ReO x is an efficient catalyst for the synthesis of adipic acid ester from cellulose-derived glucaric acid. Abstract : Synthesis of adipic acid, a key monomer of nylon-66 and polyurethane, from biomass is highly attractive for establishing green and sustainable chemical processes. Here, we report that zirconia-supported rhenium oxide (ReO x /ZrO2 ) efficiently catalyses the deoxydehydration of cellulose-derivedd -glucaric acid, offering adipic acid ester with a yield of 82% by combining with a Pd/C catalyst in subsequent reactions.